1999
DOI: 10.1007/bf02996845
|View full text |Cite
|
Sign up to set email alerts
|

Malignant schwannoma of the sinonasal tract

Abstract: Malignant Schwannoma of the sinonasal tract is an extremely rare tumour. So far, only 19 cases have been reported in the literature. We report herein a case of malignant schwannoma involving nasal cavity, maxillary antrum and ethmoid sinus in a 60-year-old male patient. The patient was treated with surgery and post-operative radiotherapy. He currently remains free of the disease 15 months after the diagnosis and twelve months after completing therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This too is rare having been described in probably fewer than 100 cases. 5 The presence of signi cant Bence Jones proteinuria in our case suggested multiple myeloma. Amyloidosis frequently presents with head and neck symptoms and is characterized by the deposition of insoluble proteinaceous material which has typical staining properties with Congo Red displaying apple green birefringence when viewed under polarized light.…”
Section: Discussionmentioning
confidence: 52%
“…This too is rare having been described in probably fewer than 100 cases. 5 The presence of signi cant Bence Jones proteinuria in our case suggested multiple myeloma. Amyloidosis frequently presents with head and neck symptoms and is characterized by the deposition of insoluble proteinaceous material which has typical staining properties with Congo Red displaying apple green birefringence when viewed under polarized light.…”
Section: Discussionmentioning
confidence: 52%
“…Head and neck schwannomas rarely occur in the sinonasal cavities, and they are typically described as solitary encapsulated lesions confined to the nasoethmoid region. [1][2][3][4][5][13][14][15][16][17] The less common cellular schwannoma has been described in the sinonasal tract, and the lack of encapsulation along with bony erosion of this variant was previously noted. 11,16 Although schwannomas are uncommon in this location, and cellular schwannomas even more so, the recognition of this entity in this anatomical site is important.…”
Section: Discussionmentioning
confidence: 99%
“…11,16 Although schwannomas are uncommon in this location, and cellular schwannomas even more so, the recognition of this entity in this anatomical site is important. [1][2][3][4][5][13][14][15][16][17] The reported case reiterates the potential risk of rendering a malignant diagnosis on biopsy, particularly in light of the aggressive radiographic findings. Although bone erosion is well described in cellular schwannomas at a variety of anatomical locations, it appears that those arising in this anatomical site tend to have the additional aggressive feature of being nonencapsulated with an infiltrative growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patient refused PET-CT to rule out a metastasis, he agreed to a biopsy of the neoplasm in his right lung, and the pathological result was a squamous carcinoma instead of a schwannoma. Schwannomas rarely metastasize to regional lymph nodes, and distant metastases are infrequent [23]. The literature has reported that distant metastases might involve the lungs, and they are associated with intracranial invasion [24].…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which erosion of the osseous walls is shown by CT or MRI, schwannomas could give the wrong impression of invasive malignant tumors. Actually, they are generally benign and hardly ever undergo malignant changes [7,8]. Most cases of schwannomas occur between the 2nd and 5th decade of life and have no gender or race predilection.…”
Section: Discussionmentioning
confidence: 99%